Efficient Inverted Perovskite Solar Cells by Employing N‐Type (D–A1–D–A2) Polymers as Electron Transporting Layer. Issue 29 (29th October 2018) - Said, Ahmed Ali; Xie, Jian; Wang, Yang; Wang, Zongrui; Zhou, Yu; Zhao, Kexiang; Gao, Wei‐Bo; Michinobu, Tsuyoshi; Zhang, Qichun
Abstract: It is highly desirable to employ n‐type polymers as electron transporting layers (ETLs) in inverted perovskite solar cells (PSCs) due to their good electron mobility, high hydrophobicity, and simplicity of film forming. In this research, the capability of three n‐type donor–acceptor1 –donor–acceptor2 (D–A1 –D–A2 ) conjugated polymers (pBTT, pBTTz, and pSNT) is first explored as ETLs because these polymers possess electron mobilities as high as 0.92, 0.46, and 4.87 cm 2 (Vs) −1 in n‐channel organic transistors, respectively. The main structural difference among pBTT, pBTTz, and pSNT is the position of sp 2 ‐nitrogen atoms (sp 2 ‐N) in the polymer main chains. Therefore, the effect of different substitution positions on the PSC performances is comprehensively studied. The as‐fabricated p–i–n PSCs with pBTT, pBTTz, and pSNT as ETLs show the maximum photoconversion efficiencies of 12.8%, 14.4%, and 12.0%, respectively. To be highlighted, pBTTz‐based device can maintain 80% of its stability after ten days due to its good hydrophobicity, which is further confirmed by a contact angle technique. More importantly, the pBTTz‐based device shows a neglected hysteresis. This study reveals that the n‐type polymers can be promising candidates as ETLs to approach solution‐processed highly‐efficient inverted PSCs. Abstract : The sp 2 ‐nitrogen positions in the n‐type (D–A1 –D–A2 ) conjugated polymers have a significant impact on the photovoltaic properties of p–i–n perovskite solar cells when they are used as an electron transporting layer. pBTTz with the HOMO and LUMO levels well‐matched with the valence and conduction bands of the perovskite layer, respectively, shows excellent power conversion efficiency and high stability.